FISH OIL PRODUCTION FROM FISH PROCESSING BY-PRODUCT BY WET-RENDERING METHOD IN DEPARTMENT OF FISHERY PRODUCT KASETSART UNIVERSITY, THAILAND - VINNY NABILA SURYA PERMATA, 141411131043 (Fakultas Perikanan dan Kelautan, 2017)
Fish by-product are usually not well-utilized. The potential of utilizing fish by-product is possible with all fish parts, one of the parts is head. Fish head could be extracted into fish oil. Fish oil could be extracted by several methods, one of them is thermal process, especially wet rendering. The yield of Pangasius head fish oil was higher than other species. However, fish oil characteristics must be considered because there are safety use standards. Pangasius head crude oil had acid value (AV) and p-anisidine value (p-AV) that match with the standards. Meanwhile, peroxide value (PV) of crude oil was lower than semi-refined oil. The oil colour result was determined and compared between crude oil and semi-refined oil.